Building Relationships Early: Banks in Venture Capital - Hellmann, Thomas; Lindsey, Laura; Puri, Manju (Review of Financial Studies, 2008)
This paper examines bank behavior in venture capital. It considers the relation between a bank's venture capital investments and its subsequent lending, which can be thought of as intertemporal cross-selling. Theory suggests that unlike independent venture capital firms, banks may be strategic investors who seek complementarities between venture capital and lending activities. We find evidence that banks use venture capital investments to build lending relationships. Having a prior relationship with a company in the venture capital market increases a bank's chance of subsequently granting a loan to that company. Companies can benefit from these relationships through more favorable loan pricing. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For permissions, please email: journals.permissions@oxfordjournals.org., Oxford University Press.